2003
DOI: 10.1097/00001813-200302000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer alkyl-lysophospholipids inhibit the phosphatidylinositol 3-kinase–Akt/PKB survival pathway

Abstract: Synthetic alkyl-lysophospholipids (ALPs) represent a new class of anti-tumor agents that target cell membranes and induce apoptosis. However, the exact mechanisms by which ALPs exert these effects remain unclear. Here, we investigated in the epithelial carcinoma cell lines A431 and HeLa the effect of three clinically relevant ALPs [Et-18-OCH3 (Edelfosine), HePC (Miltefosine) and D-21266 (Perifosine)] on the phosphatidylinositol 3-kinase (PI3K)-Akt/PKB survival pathway. We found that growth factor-induced Akt/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
0
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(166 citation statements)
references
References 52 publications
6
148
0
12
Order By: Relevance
“…Perifosine (NSC 639966/D-21266 compound 31, Figure 5) appears to block the activation and phosphorylation of Akt in cellular settings (Kondapaka et al, 2003;Ruiter et al, 2003). Perifosine is an alkylphosphocholine structurally related to miltefosine, but has an improved tolerability profile with regard to the dose-limiting gastrointestinal side effects reported for the latter.…”
Section: Phospholipids-antagonists Of Ph Domainsmentioning
confidence: 99%
“…Perifosine (NSC 639966/D-21266 compound 31, Figure 5) appears to block the activation and phosphorylation of Akt in cellular settings (Kondapaka et al, 2003;Ruiter et al, 2003). Perifosine is an alkylphosphocholine structurally related to miltefosine, but has an improved tolerability profile with regard to the dose-limiting gastrointestinal side effects reported for the latter.…”
Section: Phospholipids-antagonists Of Ph Domainsmentioning
confidence: 99%
“…Miltefosine has been reported to inhibit Akt/PKB phosphorylation leading to cell death in A431 and HeLa cell lines [5]. To investigate whether miltefosine causes similar effect(s) in skeletal muscle cells, differentiated L6E9 cells were pretreated with different concentrations of miltefosine for 30 min and subsequent insulin-stimulated activity was determined by Western immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…[1,3,4]. Although no consensus has emerged regarding the mode of action of miltefosine in cancer cells or in parasites, several likely intracellular targets related to signal transduction and lipid biosynthesis have been identified [1,5]. Using A431 and HeLa cell lines, it has been reported that miltefosine inhibits the phosphatidylinositol 3-kinase (PI3K)-Akt/protein kinase B (PKB) pathway [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain differences in the biological activity of modified alkylphospholipids as found in the study by Mravljak et al (17) which confirms our results of reduced sensitivity of MCF-7 cells to treatment with perifosine. It is crucial to determine whether prolonged treatment with perifosine induces any changes in the LFG expression since perofisone is a known regulator of survival and proliferation pathways, such as PI3K/Akt and ERK 1/2 (7,18,19). Previously, we demonstrated that LFG is a new target gene of the Akt/LEF-1 pathway (6) and consequently a potential target of perifosine activity as well.…”
Section: A B C Dmentioning
confidence: 99%